Pediatric Orthopedic Injuries Following an Earthquake: Experience in an Acute-Phase Field Hospital. Issue 4 (July 2015) - Bar-On, Elhanan; Lebel, Ehud; Blumberg, Nehemia; Sagi, Rami; Kreiss, Yitshak
Abstract : Background: Following the 2010 earthquake in Haiti, the Israel Defense Forces Medical Corps deployed a field hospital in Port au Prince. The purpose of this study was to characterize the injuries sustained by the pediatric population treated in the hospital and examine the implications for planning deployment in future similar disasters. Methods: Medical records of children treated in the hospital were reviewed and compared with medical records of the adult population. Results: A total of 1, 111 patients were treated in the hospital. Thirty-seven percent were aged 0 to 18 years. Earthquake-related injuries were the cause of admission in 47% of children and 66% of adults. Forty-seven percent of children with traumatic injuries sustained fractures. Seventy-two percent were in the lower limbs, 19% were in the upper limbs, and 9% were in the axial skeleton, with the femur being the most common long bone fractured compared with the tibia in adults. There were four functional operating theaters, and treatment guidelines were adjusted to the rapidly changing situation. Soft tissue injuries were treated by aggressive debridement. Fractures were stabilized by external fixation or casting. Amputation was performed only for nonviable limbs or life-threatening sepsis. Children were more likely than adults to undergo surgery (44% vs. 29% of trauma patients). To maximize hospital surge capacity, minor procedures were performed in the wards under sedation, and patients were discharged after an average of 1.4 days, with subsequent follow-up in the clinic. Conclusion: Children constitute a high percentage of patients in a developing country. The epidemiology of pediatric injuries following an earthquake differs significantly from that encountered in everyday practice and compared with that in adults. Children sustain a significantly higher percentage of femoral fractures and are more likely to require surgery. The shift to nontraumatic reasons for admission occurred earlier in the pediatric population than in adults. Organizations providing post-earthquake relief are usually geared toward adult populations and will require supplementation of both manpower and equipment specifically suited for treatment of pediatric patients. Early deployment teams should be adequately staffed with adult and pediatric orthopedists. ( J Trauma Acute Care Surg. 2013;74: 617–621. Copyright © 2013 by Lippincott Williams & Wilkins) Level of Evidence: Epidemiologic study, level IV.